Human Resource Development and Its Impact on Employee Performance is Mediated by Innovative Behavior in Employees of the Tirta Yaponno Ambon Regional - Sijabat, Asiani; Lewaherilla, Novalien Carolina; Chandra, Felix; Noya, Rylano Stefano; Hadinda, Hadinda (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
This study aims to analyze the influence of human resource development and its impact on employee performance, as well as to examine the mediated influence of innovation behavior on employees of Perumdam Tirta Yapono Ambon. The population in this study was 35 employees, with the entire population being sampled. Data were collected using the SmartPLS analysis tool. The results showed thatHuman resource development has no significant effect on employee performance. Furthermore, human resource development has a significant effect on innovation behavior. Innovation behavior has a significant effect on employee performance.Furthermore, there is an influence between human resource development and performance through innovation behavior as a mediating variable. Based on the results of this study, it is hoped that the Tirta Yaponno Ambon Regional Public Works Office will pay more attention to employee human resource development and that employees must be more proactive and produce innovative behaviors to improve performance